1981
DOI: 10.1177/00220345810600031801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro and in vivo Dog Dentin Permeability

Abstract: A method is described which permits the quantitation of the rate of permeation of 131I through dog dentin, both in vivo and in vitro. The results demonstrate the rapidity of the systemic appearance of substances placed on intact dentin. Comparison of the rate of permeation of 131I made in vivo and in vitro, on the same teeth, indicates the rates are very similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
15

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 14 publications
1
9
0
15
Order By: Relevance
“…This behavior is analogous to that observed in our previous report, that the permeability of dog dentin was similar when studied in vivo or in vitro, in the same teeth (Pashley et al, 1981a). These observations suggest that dentin is relatively stable over time.…”
Section: Resultssupporting
confidence: 90%
“…This behavior is analogous to that observed in our previous report, that the permeability of dog dentin was similar when studied in vivo or in vitro, in the same teeth (Pashley et al, 1981a). These observations suggest that dentin is relatively stable over time.…”
Section: Resultssupporting
confidence: 90%
“…2.5 ml was chosen as the collection volume, to allow four 0.5-ml samples from each tooth to be tested. The various data on the diffusion of known substances across dentin (Pashley et al, 1977(Pashley et al, , 1978b(Pashley et al, , 1981Hume, 1984a) indicated that one day was a reasonable initial collection time in which to expect peak availability of applied chemicals at the pulpal surface.…”
Section: Resultsmentioning
confidence: 99%
“…He demonstrated that a smear layer existing on polished surfaces, reduces water movement through the dentin tubules. [28] Surface etching resulted in lower contact angles on enamel E3(E) (Figure 2a and 3E3(E)). On dentin the contact angle is decreased only for water D3(E) (Figure 2b and 3D3(E)).…”
Section: Wettabilitymentioning
confidence: 92%